Determination Of IgE Levels In Allergies Among Medical Laboratory Technology Students In Universitas Muhammadiyah Purwokerto - SUDARSONO, TANTRI ANALISAWATI; KUSUMA WARDANI, DITA PRATIWI; MULYANTO, ARIF (Pena Medika Jurnal Kesehatan, 2021)
The prevalence of allergies is increasing from year to year due to the modern lifestyle in society. The incidence of allergies was influenced by several factors, such as genetics, age, sex, diet, food type, and also environmental factors. Determination Ig E levels in adolescents and young adults is important because the incidence of allergy is highly reported in adolescents and young adults. This study was conducted to determine Ig E levels in allergies among university students in Universitas Muhammadiyah Purwokerto This observational study was conducted among diploma students of Medical Laboratory Technology, Universitas Muhammadiyah Purwokerto. The data of characteristic subjects were collected by a self-administered questionnaire whereas data of Ig E levels were collected by serum samples and measured by ELISA. A total of 23 students (4,35 % male and 95,65% female) were included. Seafood allergy (25%) were the commonest allergy among the students. Only 9% of subjects have combination allergies. The highest of Ig E levels were 365 IU/mL.